2023
DOI: 10.1088/1361-6560/acc7e0
|View full text |Cite
|
Sign up to set email alerts
|

The development and characterization of an all-purpose bolus for radiotherapy

Abstract: Objective. The purpose of this study was to develop a new bolus (HM bolus), with tissue equivalence, transparency, reusability, and free shaping at approximately 40 °C for excellent adhesion, and to evaluate the feasibility of clinically using this bolus as an ideal bolus. Approach. We summarized the advantages and disadvantages of existing boluses. To evaluate dose characteristics, a vinyl gel sheet bolus (Gel bolus) and HM bolus placed on a water-equivalent phantom were used to obtain the percent depth dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…The thickness of the HM bolus and gel-sheet bolus was 5 mm. Experiments were performed using the same geometry as reported by Nakamura et al [9]. The PDD results are shown in Figure 2, which indicate that the HM bolus agreed with the gel-sheet bolus within 1% of the dose difference.…”
Section: Case Presentationmentioning
confidence: 66%
See 3 more Smart Citations
“…The thickness of the HM bolus and gel-sheet bolus was 5 mm. Experiments were performed using the same geometry as reported by Nakamura et al [9]. The PDD results are shown in Figure 2, which indicate that the HM bolus agreed with the gel-sheet bolus within 1% of the dose difference.…”
Section: Case Presentationmentioning
confidence: 66%
“…We have developed a shapeable soft-rubber bolus and reported its adherence to a head-phantom [8]. Nakamura et al (2023) reported an HM bolus with improved temperature characteristics and transparency, which were limitations of the existing soft-rubber boluses [9]. This report describes the first clinical use of the HM bolus in a patient with a cSCC of the cheek.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantage of these customized 3D printed compensators is that they fit closely with the skin, with very small gaps between them, ensuring that the planned dose is relatively close to the actual dose. 6 However, the downside is the high technical requirements and cost involved. As a result, many hospitals may not have the capacity to provide individual compensators for each patient.…”
Section: Introductionmentioning
confidence: 99%